2011
DOI: 10.1016/j.ijgo.2011.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni infection among prenatal attendees at a secondary‐care hospital in central Sudan

Abstract: There was a high level of S. mansoni infection among pregnant women in the present setting, especially among younger women and those with no education. Control and preventive measures should be used in the area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…The 21.1 % prevalence of S. haematobium recorded showed that it is of a high public health importance in the group as the disease will not only impair the health of the mother but also of the growing fetus. This estimate is higher than the earlier prevalence report 13.0 % by Khalid et al (2012) in central Sudan but slightly lower than the 23.8 % prevalence reported by Eyo et al (2012) in Southeastern part of Nigeria. The role of age of women in the transmission of schistosomiasis has earlier been discussed in our previous study (Salawu and Odaibo 2013b).…”
Section: Discussioncontrasting
confidence: 68%
“…The 21.1 % prevalence of S. haematobium recorded showed that it is of a high public health importance in the group as the disease will not only impair the health of the mother but also of the growing fetus. This estimate is higher than the earlier prevalence report 13.0 % by Khalid et al (2012) in central Sudan but slightly lower than the 23.8 % prevalence reported by Eyo et al (2012) in Southeastern part of Nigeria. The role of age of women in the transmission of schistosomiasis has earlier been discussed in our previous study (Salawu and Odaibo 2013b).…”
Section: Discussioncontrasting
confidence: 68%
“…We found that helminths detected by PCR were associated with previously described risk factors for helminth infection, including agricultural occupation[22,23], lack of piped water[22], and low educational level[15,19,21,22]. Importantly, we failed to detect these associations when infection status was determined by microscopy.…”
Section: Discussionmentioning
confidence: 55%
“…Studies using microscopy to evaluate risk factors associated with helminth infections have found associations with age[14-20], gender[16,17], education[15,19,21,22], farming occupation[22,23], rural habitation[22,24,25] and poor hygiene practices[16]. In addition, microscopy-identified helminth infections have been associated with anemia[2,26-28], micronutrient deficiency[4], reduced physical fitness and worker productivity[5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies carried out in many parts of Sudan, different prevalences of S. mansoni infection have been recorded, e.g. in Wadi Halfa (ancient Nubia) was 26.1% [12] , in central Sudan was 13% prevalence among pregnant women [13] and was 36.7% among schoolchildren [19] . Furthermore, worldwide studies have been determined the prevalence of S. mansoni infection.…”
Section: Discussionmentioning
confidence: 99%
“…In Sudan, the high endemicity of S. mansoni infections have been reported in many parts of the country [12][13][14] . Therefore, the first approach for prevention and control is to diagnose the disease through applying different laboratory methods.…”
Section: Introductionmentioning
confidence: 99%